Rational Design of Metal Halide Perovskite Nanocrystals for Photocatalytic CO2 Reduction: Recent Advances, Challenges, and Prospects - Wang, Jin; Shi, Yangyi; Wang, Yuhan; Li, Zhengquan (ACS energy letters, 2022)
Metal halide perovskite nanocrystals (MHP NCs) have attracted much scientific interest in photocatalysis. Various types of MHP photocatalysts have been intensively explored in photocatalytic CO2 reduction in the past few years. However, some key issues, such as severe charge recombination, low stability, and the origin of products, have created bottlenecks in developing MHP photocatalysts. Therefore, the rational design of MHPs is worthwhile to deepen our understanding of the above issues and develop efficient photocatalysts. This Focus Review highlights the recent advances in MHP photocatalysts regarding design principles toward photocatalytic CO2 reduction. Various modification strategies are clarified, and an outlook on future challenges and prospects is also provided to point out the possible research directions in MHP photocatalysts. It is anticipated that this Focus Review can provide guidance on the design of MHP-based photocatalysts and help uncover some common issues encountered by the scientific community when studying MHP photocatalysts.